2023
DOI: 10.3390/catal13020283
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Modeling of the Catalytic Aquathermolysis Process to Evaluate the Efficiency in a Porous Medium by the Example of a Carbonate Extra-Viscous Oil Field

Abstract: In order to evaluate the efficiency of the catalytic aquathermolysis process, physical modeling was carried out on bituminous sediments of Paleocene–Miocene carbonate rocks, characterized by the presence of open and closed fractures. In this context, three filtration experiments were performed on an unextracted reservoir model with extra-viscous oil (EVO). Prior to the experiments, the mineral composition of the rock was determined by X-ray diffraction analysis (XRD) and the content of organic matter and cokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Studies to assess the dynamics of decomposition of the heat-and gas-generating system during the flooding of the salt composition and initiating the additives in the oil-saturated pore space were carried out on a filtration unit, described in more detail in [4,11,23,24].…”
Section: Filtration Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies to assess the dynamics of decomposition of the heat-and gas-generating system during the flooding of the salt composition and initiating the additives in the oil-saturated pore space were carried out on a filtration unit, described in more detail in [4,11,23,24].…”
Section: Filtration Experimentsmentioning
confidence: 99%
“…Initially, oil production is carried out using the natural driving force of the reservoir (primary production), and it is then possible to use other sources of energy in the reservoir (secondary oil recovery/waterflooding). In this regard, in order to increase the oil recovery of the residual oil remaining in mature hydrocarbon reservoirs in the future, tertiary methods need to be used [2][3][4]. Experience throughout the world has shown that the most common and effective methods for recovering heavy and extra heavy oil are thermal methods [5] and their various modifications [6,7].…”
Section: Introductionmentioning
confidence: 99%